ANALISA PERANAN ANGGARAN BIAYA OPERASIONAL SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN LABA : STUDI KASUS PADA PT. ADHYA TIRTA BATAM - Jaya, Hendry (MEASUREMENT : Jurnal Program Studi Akuntansi, 2014)
Purpose of this research is conducted to determine whether the operational budget has served as a means of profit planning and control on PT. Adhya Tirta Batam.            Data analysis methods used  is descriptive qualitative research method, a way to collect data form the PT. Adhya Tirta Batam to support this paper to be interpreted, so that it can provide an objective picture of  the object and the issue examined.             The results of research by the author explained that PT.Adhya Tirta Batam has made operational budget preparation procedure well and effectively, by the method of bottom-up budgeting. The results of this study also indicate that the operational budget has played well and ineffectively as a means of profit planning and control in PT. Adhya Tirta Batam. This is shown by the analysis of the authors, using analysis of variance or deviation between actual with predetermined budgets. The difference in deviation from the year 2011-2012 was an aberration "profitable" in 2013 is deviation "unfortunate", but the difference is still in the normal category or difference which still can be controlled companies.